2014
DOI: 10.1016/j.ijid.2014.03.1395
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between single nucleotide polymorphisms of pulmonary surfactant protein A gene and pulmonary tuberculosis in the Han population in China

Abstract: SNP in SP-A is associated with PTB in the Han population in China. The G allele at aa91, T allele at aa140, and haplotype 6A11-1A8 are risk factors for PTB, but haplotype CGAAC-1A(0) and 6A(4)-1A(12) are protective factors for PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…In a Chinese population, the polymorphism 1649G in the SP-A2 gene was strongly associated with tuberculosis, mirroring the findings in the Ethiopian and Indian populations (Yang et al 2014). The SP-A2 1649G leads to a transversion (proline to alanine), affecting the triple helical structure of SP-A (Yang et al 2014). In SP-D, the polymorphism, G459A, is significantly associated with tuberculosis susceptibility in an Indian population, but the molecular basis for susceptibility is not understood (Vaid et al 2006).…”
Section: Sp-a and Sp-dsupporting
confidence: 71%
See 2 more Smart Citations
“…In a Chinese population, the polymorphism 1649G in the SP-A2 gene was strongly associated with tuberculosis, mirroring the findings in the Ethiopian and Indian populations (Yang et al 2014). The SP-A2 1649G leads to a transversion (proline to alanine), affecting the triple helical structure of SP-A (Yang et al 2014). In SP-D, the polymorphism, G459A, is significantly associated with tuberculosis susceptibility in an Indian population, but the molecular basis for susceptibility is not understood (Vaid et al 2006).…”
Section: Sp-a and Sp-dsupporting
confidence: 71%
“…Another study also found two polymorphisms (SP-A2 G1649C and SP-A2 A1660G) in the introns of SP-A1 that were associated with tuberculosis in an Indian population, but none in the SP-A1 gene (Madan et al 2002). In a Chinese population, the polymorphism 1649G in the SP-A2 gene was strongly associated with tuberculosis, mirroring the findings in the Ethiopian and Indian populations (Yang et al 2014). The SP-A2 1649G leads to a transversion (proline to alanine), affecting the triple helical structure of SP-A (Yang et al 2014).…”
Section: Sp-a and Sp-dmentioning
confidence: 60%
See 1 more Smart Citation
“…Positive samples were then evaluated by employing the Mycobacterial Growth Indicator Tube 960 broth system culture (MGIT, Becton Dickinson, Franklin Lakes, USA) using the following concentrations: 4 first line anti-TB drugs, isoniazid (INH) 0.2 μg/ml, rifampin (RFP) 1.0 μg/ml, streptomycin (SM) 2.0 μg/ml, ethambutol (EMB) 7.5 μg/ml; and 7 second line anti-TB drugs, ofloxacin (Ofx) 2.0 μg/ml, capreomycin (Cm) 20.0 μg/ml, kanamycin (Km) 30.0 μg/ml, amikacin (Am) 40.0 μg/ml, paminosalicylic acid (PAS) 2.0 μg/ml, ethionamide (Eto) 40.0 μg/ml and cycloserine (Cs) 40.0 μg/ml. Isolates were considered resistant to a particular drug if the growth rate was more than 1% compared with the control or sensitive if the growth rate was less than 1% compared with the control [ 7 , 14 ]. The definition of MDR TB is a strain that is resistant to at least two first-line drugs (INH and RFP).…”
Section: Methodsmentioning
confidence: 99%
“…SNPs in the SFTPA1 and SFTPA2 genes encoding pulmonary surfactant protein A (SPA) were found to be associated with pulmonary tuberculosis in the Han population in China. The G allele of rs17886395, T allele of rs1965707 and haplotype CCAAC–CGCA in combination with SFTPA1 and SFTPA2 were found to be risk factors, while haplotype CGAAC ( SFTPA1 ) – AGCC ( SFTPA2 ) and TCGAT- ACCC were found to be protective for pulmonary tuberculosis (Yang et al, 2014a). In other study the T allele of rs1914663 in the SFTPA gene was found to associate with increased risk of TB, whereas the TC+TT genotype was found to be higher in PTB and non-severe TB, as compare to controls, in the Han Chinese population (Li et al, 2016) (Table 1).…”
Section: Introductionmentioning
confidence: 99%